DETERMINANTS OF CAPITAL STRUCTURE: A STUDY OF FERTILIZER INDUSTRY OF PAKISTAN - Jahangir Tanveer; Dr. Musarrat Shamshir; Dr. Shahzad Nasim; Sidra Nisar; Dr. Salman Ahmed Shaikh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The capital structure of a firm determines the ability to raise the capital of the firm by impacting market price and earnings per share for the shareholder.Capital structure is a mixture of debt and equity such that to choose from different options available to the organization for financing its assets. Higher leverage implies an increase in total earnings of the firm due to the excess of earnings on borrowing than the interest payment on debts. Both in financial and non-financial sectors, researchers find it interesting to determine the attributes that impact capital structureThe current study aims at investigating the relationship of profitability, size, growth, and tangibility with leverage and their significance in determining the capital structure of the firm by using the data from 2010-2019, of the fertilizer industry in Pakistan by considering all six firms in the industry, listed in Pakistan stock exchange; namely, Engro Fertilizers; Fatima Fertilizers, FaujiFertilizer Corporation, Fauji Fertilizer bin Qasim Ltd and Pak Arab Fertilizer. Hausman specification test is applied to check the appropriation of model among fixed and random effect. The findings revealed the significance of all the variables. Profitability, size, and tangibility were found negatively correlated while growth was found to be positively correlated with leverage. JEL code: G32